In situ CRISPR‐Cas9 base editing for the development of genetically engineered mouse models of breast cancer. (13th January 2020) - Annunziato, Stefano; Lutz, Catrin; Henneman, Linda; Bhin, Jinhyuk; Wong, Kim; Siteur, Bjørn; van Gerwen, Bas; de Korte‐Grimmerink, Renske; Zafra, Maria Paz; Schatoff, Emma M; Drenth, Anne Paulien; van der Burg, Eline; et al.
Abstract: Genetically engineered mouse models (GEMMs) of cancer have proven to be of great value for basic and translational research. Although CRISPR‐based gene disruption offers a fast‐track approach for perturbing gene function and circumvents certain limitations of standard GEMM development, it does not provide a flexible platform for recapitulating clinically relevant missense mutations in vivo . To this end, we generated knock‐in mice with Cre‐conditional expression of a cytidine base editor and tested their utility for precise somatic engineering of missense mutations in key cancer drivers. Upon intraductal delivery of sgRNA‐encoding vectors, we could install point mutations with high efficiency in one or multiple endogenous genes in situ and assess the effect of defined allelic variants on mammary tumorigenesis. While the system also produces bystander insertions and deletions that can stochastically be selected for when targeting a tumor suppressor gene, we could effectively recapitulate oncogenic nonsense mutations. We successfully applied this system in a model of triple‐negative breast cancer, providing the proof of concept for extending this flexible somatic base editing platform to other tissues and tumor types. Synopsis: Most human cancers, including breast cancer, are predominantly characterized by missense mutations in driver genes. This study describes a genetically engineered mouse model, in which conditional expression of the BE3 cytidine base editor in the adult mammary gland permits installation of missense or nonsense mutations at one or multiple genomic loci. Introduction of point mutations in endogeneous genes by CRISPR‐Cas9‐mediated base editing allows for assessment of their contribution to mammary tumor formation. Rapid somatic engineering of allelic series of oncogenic missense mutations determines the relative effect size of each genetic perturbation. Biallelic inactivation of endogenous tumor suppressor genes by base editing, although bystander indels are also observed. Simultaneous base editing at multiple genomic loci using arrayed sgRNA vectors. Abstract : A new knock‐in mouse model allows for Cre‐mediated conditional expression of the BE3 cytidine base editor and in vivo analysis of somatic missense mutations.